Electrical Field-Assisted Gene Delivery from Polyelectrolyte Multilayers - Yu-Che Cheng (Polymers, 2020)
To sustain gene delivery and elongate transgene expression, plasmid DNA and cationic nonviral vectors can be deposited through layer-by-layer (LbL) assembly to form polyelectrolyte multilayers (PEMs). Although these macromolecules can be released for transfection purposes, their entanglement only allows partial delivery. Therefore, how to efficiently deliver immobilized genes from PEMs remains a challenge. In this study, we attempt to facilitate their delivery through the pretreatment of the external electrical field. Multilayers of polyethylenimine (PEI) and DNA were deposited onto conductive polypyrrole (PPy), which were placed in an aqueous environment to examine their release after electric field pretreatment. Only the electric field perpendicular to the substrate with constant voltage efficiently promoted the release of PEI and DNA from PEMs, and the higher potential resulted in the more releases which were enhanced with treatment time. The roughness of PEMs also increased after electric field treatment because the electrical field not only caused electrophoresis of polyelectrolytes and but also allowed electrochemical reaction on the PPy electrode. Finally, the released DNA and PEI were used for transfection. Polyplexes were successfully formed after electric field treatment, and the transfection efficiency was also improved, suggesting that this electric field pretreatment effectively assists gene delivery from PEMs and should be beneficial to regenerative medicine application.